2017
DOI: 10.1017/jfm.2017.390
|View full text |Cite
|
Sign up to set email alerts
|

The turbulence cascade in the near wake of a square prism

Abstract: We present a study of the turbulence cascade on the centreline of an inhomogeneous and anisotropic near field turbulent wake generated by a square prism at Re = 3900 using the Kármán-Howarth-Monin-Hill (KHMH) equation. This is the fully generalised scale-by-scale energy balance which, unlike the Kármán-Howarth equation, does not require homogeneity or isotropy assumptions. Our data are obtained from a direct numerical simulation (DNS) and therefore enable us to access all the processes involved in this energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 65 publications
9
84
1
Order By: Relevance
“…In the strongly non-isotropic near field of the wake studied by Portela et al [35], an amplification of energy was observed in the energy-containing subrange (see model spectrum 2 in Fig. 10 a); this is associated with coherent structures (vortex shedding).…”
Section: The Physical Meaning Of (T Br ) Asmentioning
confidence: 81%
See 1 more Smart Citation
“…In the strongly non-isotropic near field of the wake studied by Portela et al [35], an amplification of energy was observed in the energy-containing subrange (see model spectrum 2 in Fig. 10 a); this is associated with coherent structures (vortex shedding).…”
Section: The Physical Meaning Of (T Br ) Asmentioning
confidence: 81%
“…The model spectrum 2 is obtained with Eq. (3.4) in [35] and represents a 1-D energy spectrum amplified in the energy-containing subrange.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…Note that it has been assumed that all out-of-plane gradients of the mean velocity field vanish due to the flow's symmetry (measurements are taken at the flume's mid-plane) as well as out-of-plane gradients of the coherent velocity fluctuations (this can be supported by a recent study of Portela et al [47] who performed direct numerical simulation of a flow past a rectangular prism at comparable Reynolds number).…”
Section: Energy Budgetmentioning
confidence: 94%
“…Near the impeller, turbulence intensities grow significantly, possibly explaining why the -5/3 slope is not that clear there (see fig 14). In any case, the -5/3 slope in temporal spectra has been observed even in flow cases where the Kolmogorov theory conditions for its existence are very far from being met [24][25][26] which means that its underlying cause remains fundamentally unexplained not only in our flow but also in general.…”
Section: Turbulence Distribution Across Scalesmentioning
confidence: 99%